Circulating vaspin levels and epicardial adipose tissue thickness are associated with impaired coronary flow reserve in patients with nonalcoholic fatty liver disease - EREN, FATİH; ÖZEN ALAHDAB, YEŞİM; YILMAZ, YUSUF (ELSEVIER IRELAND LTD, 2011)
Background: Patients with nonalcoholic fatty liver disease (NAFLD) have a reduced coronary flow reserve (CFR) and an increased risk of cardiovascular disease. The fat cells that surround coronary arteries may play a central and underrecognized role in development of cardiovascular disease through the systemic secretion of adipokines. We therefore evaluated the relation of epicardial fat thickness, serum levels of epicardial fat-related adipokines (chemerin and vaspin), and CFR in patients with NAFLD. Methods: We investigated 54 patients with biopsy-proven NAFLD and 56 age- and sex-matched controls. CFR and epicardial fat thickness (EFT) were measured by transthoracic echocardiography. Serum levels of chemerin and vaspin were measured by ELISA. Results: EFT was significantly higher (0.64 +/- 0.13 vs. 0.54 +/- 0.10 cm, P < 0.001) and CFR significantly lower (2.11 +/- 0.45 vs. 2.52 +/- 0.62, P < 0.001) in patients with NAFLD than in controls. Serum levels of vaspin and chemerin were both significantly increased in patients with NAFLD compared with controls. Stepwise regression analysis showed that EFT (beta = -0.53, t = -3.7, P < 0.001), serum vaspin levels (beta = -0.30, t = -2.5, P = 0.014), and liver fibrosis (beta = -0.31, t = -2.11, P = 0.041), in the order they entered into the model, were independent predictors of CFR in NAFLD patients. Conclusion: Our data suggest the presence of a complex interplay between EFT, serum vaspin, and liver histology in promoting an impaired hyperemic stimulation of coronary blood flow in patients with NAFLD. (C) 2011 Elsevier Ireland Ltd. All rights reserved.
Keywords: Biomarkers; Epicardial fat thickness; Coronary flow reserve; Adipokines; Nonalcoholic fatty liver disease; METABOLIC SYNDROME; SERUM-LEVELS; CHEST-PAIN; ARTERY; CHEMERIN; WOMEN; ECHOCARDIOGRAPHY; INFLAMMATION; MARKER; RISK